SDG Convergence or Divergence? Indonesia’s Development Trajectory Among Emerging Economies and the Path Toward OECD Standards (2000–2025) - Setia Damayanti; Eka Sudarmaji; Lely Mustika; Norngainy Mohd Tawil (Institute of Multidisciplinary Research and Community Service, 2026)
Despite Indonesia’s stated commitment to the 2030 Agenda, the quantitative distance between its SDG performance and OECD benchmarks has received surprisingly little systematic attention. This paper closes that gap by extending a comparative convergence analysis of Indonesia against 14 emerging-economy peers, using panel data for 167 countries from 2000 to 2025, two years further than any prior published study. Four methods are applied sequentially: sigma-convergence analysis using the coefficient of variation, beta-convergence estimation via ordinary least squares regression, K-means cluster analysis across 17 SDG dimensions, and an OECD Gap–Momentum Priority Matrix constructed from Lasso regression and Spearman rank correlation. The results confirm sigma-convergence among the peer group (CV falling from 9.58% in 2000 to 6.97% in 2025). However, Indonesia’s own beta-convergence coefficient remains statistically tenuous (β = 0.064, p = 0.071), pointing to structural inertia rather than purposeful catch-up. The Kruskal-Wallis test confirms that regional score differences are not random variation (H = 127.34, p 0.001). Indonesia’s largest absolute deficits lie in SDG 9 (Industry, Innovation, and Infrastructure; gap = 34.5 points), SDG 3 (Good Health; 25.8 points), and SDG 15 (Life on Land; 21.9 points). However, with an annual progress rate of 0.851 points (the fastest recorded among all 15 peers), Indonesia is on track to close the OECD gap within roughly 11 years at the current pace. SDGs 9, 3, and 5 are identified as the highest-return targets for concentrated policy effort given their combination of structural weight and persistent underperformance. Keywords: SDG convergence, OECD benchmark, Sustainable development.